Perturbation of RNA Polymerase I transcription machinery by ablation of HEATR1 triggers the RPL5/RPL11-MDM2-p53 ribosome biogenesis stress checkpoint pathway in human cells - Turi, Zsofia; Senkyrikova, Marketa; Mistrik, Martin; Bartek, Jiri; Moudry, Pavel (Cell cycle (Georgetown, Tex.), 2018)
Ribosome biogenesis is an energy consuming process which takes place mainly in the nucleolus. By producing ribosomes to fuel protein synthesis, it is tightly connected with cell growth and cell cycle control. Perturbation of ribosome biogenesis leads to the activation of p53 tumor suppressor protein promoting processes like cell cycle arrest, apoptosis or senescence. This ribosome biogenesis stress pathway activates p53 through sequestration of MDM2 by a subset of ribosomal proteins (RPs), thereby stabilizing p53. Here, we identify human HEATR1, as a nucleolar protein which positively regulates ribosomal RNA (rRNA) synthesis. Downregulation of HEATR1 resulted in cell cycle arrest in a manner dependent on p53. Moreover, depletion of HEATR1 also caused disruption of nucleolar structure and activated the ribosomal biogenesis stress pathway - RPL5 / RPL11 dependent stabilization and activation of p53. These findings reveal an important role for HEATR1 in ribosome biogenesis and further support the concept that perturbation of ribosome biosynthesis results in p53-dependent cell cycle checkpoint activation, with implications for human pathologies including cancer.
Keywords: HEATR1; RNA-polymerasa I; Cell Line, Tumor; Cell Proliferation; Ribosomal Proteins; cancer; Transcription, Genetic; ribosome biogenesis; protoonkogenní proteiny c-mdm2; signální transdukce; vedlejší histokompatibilní antigeny; kontrolní body buněčného cyklu; biogeneze organel; jaderné proteiny; nádorový supresorový protein p53; ribozomy; RNA, Ribosomal; Proto-Oncogene Proteins c-mdm2; Signal Transduction; Stress, Physiological; genetická transkripce; p53; ribozomální proteiny; Organelle Biogenesis; Ribosomes; lidé; RNA Polymerase I; RNA ribozomální; Humans; RNA-Binding Proteins; Minor Histocompatibility Antigens; proliferace buněk; ribosome biogenesis stress; Cell Cycle Checkpoints; nádorové buněčné linie; fyziologický stres; Nuclear Proteins; Tumor Suppressor Protein p53; proteiny vázající RNA